PENGARUH PARTISIPASI PIMPINAN DAN IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KINERJA KEUANGAN (Studi pada SKPD Provinsi Bengkulu) - Ramadanti, Um Fajri; Abdillah, Willy; Robinson, Robinson (UNIB Press, 2013)
This study aimed to measure the effect of participation and leadership on the financial performance of SAP Implementation at Regional Working Units (on education) Bengkulu province. As for the number of samples in this study consisted of 86 respondents, where the questionnaire distributed to all SKPDs Bengkulu Provincial Government, to test the validity and Reliability of. Based on the results of multiple linear regression calculation on the first hypothesis, variable leadership participation a positive and significant effect on the financial performance. In the second hypothesis, the variable implementation for SAP (Government Accounting Standards) is also positive and significant effect on performance, so that the second hypothesis is accepted. Thus, Participation and leadership of SAP Implementation (Government Accounting Standards) positive and significant effect on the financial performance in the regional work units Bengkulu Provincial Government.